A Weed of Global Significance Parthenium hysterophorus L.: An Overview of two faces of Parthenium weeds. (International Journal of Food and Nutritional Sciences, 2022)
The noxious and invasive weed Parthenium hysterophorus L., commonly known as "famineweed" or "congress grass," poses significant risks to human health, agriculture, and biodiversity.Renowned for its rapid and aggressive growth, as well as allelopathic characteristics inhibiting thegrowth of natural vegetation and desirable crops, this abstract provides an overview of both thedrawbacks and potential uses of Parthenium hysterophorus. Various control methods, includingmechanical removal, chemical herbicides, introduction of biological control agents, and culturalpractices, are employed to counteract its proliferation